HUBUNGAN MOTIVASI DAN KEAKTIFAN TERHADAP KEMAMPUAN MEMBACA BAHASA INGGRIS PADA MAHASISWA FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH TANGERANG - Dwi Lestari, Rivka; Purwani, Retno; Winarni, Lastri Mei (Nusantara Hasana Journal, 2022)
Based on the preliminary study, the results of the research conducted by the researcher with 10 respondents showed that the aspects of learning motivation were 40% and 60% had less motivation. Research objectives to determine the relationship between motivation and activity on the ability to read English in students of the Faculty of Health Sciences, Muhammadiyah University, Tangerang. Research Methods: This research is a quantitative research, with a descriptive correlation research design. This study uses a cross sectional approach, which is a research design that can be measured and tried only once. The instrument used is a questionnaire and the analytical test used is the chi square test and correlation. Based on the results of the chi square test analysis, based on the chi-square test that p-value = 0.000 <0.05, it can be stated that Ha is accepted, meaning that there is a relationship between motivation and English reading ability of students at Muhammadiyah University of Tangerang.